Assessment of Storm Floods in a Small Tropical Andean Basins - Zambrano Nájera, Jeannette; Rey, Diana Marcela (Frontiers in Climate, 2022)
The increase in urbanization processes has considerably changed urban flows, as basin impermeabilization generates increased surface runoff volumes. This induces storm floods that simultaneously generate mobility problems, infrastructure damage, and in extreme conditions, pedestrian deaths. This problem has been widely studied. For small basins with steep watersheds, however, there is little literature to be found. In these basins, the problem is even more complex, as flows are faster and more energized, given the surface slopes, which generates further problems, including drainage infrastructure damage, landslides, and fallen trees. Many solutions have been proposed, which include Sustainable Urban Drainage Systems (SUDS), which work together with the drainage network. These were studied in the present investigation, via the modelling of a basin with those characteristics typical of mountains, using SWMM’s Low Impact Development LID model. It was found that rain barrels and green roofs were viable solutions, independently, although the application of additional techniques, such as cisterns and bioretention cells, is also indispensable. The present study also concludes that, although the techniques studied are implemented on a small scale, these should be both planned and implemented by municipal authorities.